THE EFFECT OF DISASTER PREPAREDNESS ON THE SOCIAL SENSITIVITY OF SOCIAL SCIENCES PRE-SERVICE TEACHERS - Amin, Saiful; Kurniawan, Muchammad Akbar; Indriyansah, Renata Tiand; Shobah, Wulan Nurus (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Social sensitivity to disasters is an act of concern carried out by someone after a disaster either in the form of real action or material assistance. The level of one's social sensitivity to disasters is assumed to be influenced by the attitude of disaster preparedness. This study aims to determine the effect between disaster preparedness on social sensitivity of prospective social studies education teachers. The approach used is quantitative with the type of correlation research. The population used in this study were all students of the Social Science Education Department, UIN Maulana Malik Ibrahim Malang, Indonesia who were taking the Geography of Disaster Course with a total of 118 people. The sample was determined as many as 91 people used in this study. Instruments in the form of questionnaires were used to measure disaster preparedness and social sensitivity of students with a Likert scale of 1-4 (strongly disagree - strongly agree). Data analysis in this study used normality test, homogeneity test, and t-test assisted by SPSS IBM 23 programme with 5% significance level. The results showed that the disaster preparedness variable had a sig value. 0,000 > 0,05. The conclusion is that disaster preparedness has a significant effect on the social sensitivity of social sciences pre-service teachers.